2019
DOI: 10.33069/cim.2019.0016
|View full text |Cite
|
Sign up to set email alerts
|

Light and Life at Night as Circadian Rhythm Disruptors

Abstract: The axial rotation of the Earth, together with the light of the sun, generates 24-hour cycles of day and night, and this light-dark cycle is the basis of 24-hour circadian rhythms. Living organisms have their own endogenous circadian rhythms, also with a duration of approximately 24 hours, driven by environmental factors, especially light and darkness [1]. And it is widely known that circadian rhythms of mammals are regulated by an internal biological clock located in the suprachiasmatic nuclei (SCN) situated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 120 publications
0
13
0
Order By: Relevance
“…A growing number of epidemiological studies have reported evidence for an association between exposure to dLAN and several pathologies, including obesity (8), breast and prostate cancer (9), increased blood pressure (10), and sleep disorders (11). Because dLAN disturbs the natural light-dark (LD) cycles, circadian clocks are considered the primary system susceptible to improper functioning, underlying the link between dLAN and increased health risks (12,13). Indeed, after chronic exposure to dLAN (≤ 5 lx), compromised circadian function has been shown experimentally through suppressed night-time melatonin levels (14,15), attenuated rhythms in locomotor activity (16) and cardiovascular parameters (14), and altered clock gene oscillations (17).…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of epidemiological studies have reported evidence for an association between exposure to dLAN and several pathologies, including obesity (8), breast and prostate cancer (9), increased blood pressure (10), and sleep disorders (11). Because dLAN disturbs the natural light-dark (LD) cycles, circadian clocks are considered the primary system susceptible to improper functioning, underlying the link between dLAN and increased health risks (12,13). Indeed, after chronic exposure to dLAN (≤ 5 lx), compromised circadian function has been shown experimentally through suppressed night-time melatonin levels (14,15), attenuated rhythms in locomotor activity (16) and cardiovascular parameters (14), and altered clock gene oscillations (17).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, artificial light is a potent circadian rhythm disruptor that reduces melatonin levels with serious consequences. [177][178][179][180] POC measurements of tryptophan and melatonin levels could enable the early diagnosis of circadian disruption-related physiological and psychological disorders. In addition, sensing both melatonin and tryptophan in real-time might provide key insights into their role in immunomodulation, inflammatory disease, and inflammatory responses to pandemic diseases such as COVID-19.…”
Section: Challenges and Future Perspectivesmentioning
confidence: 99%
“…While this statement does not necessarily preclude unnamed factors from influencing adolescent fatigue, it could be interpreted in this way. This is problematic because there is a complex interplay between developmental factors and environmental cues that affect the circadian rhythm (Lee & Kim, 2019). These environmental cues (or zeitgebers) include modifiable lifestyle factors such as natural and artificial light exposure (Roenneberg & Merrow, 2007), some of which can be adjusted for improved functioning at different stages of human development.…”
Section: Critical Analysis Of Neuromyth Itemsmentioning
confidence: 99%